PTU-206 Downstaging by further chemotherapy for poor responders to chemoradiotherapy in inoperable rectal cancers – prospective study. (22nd June 2015) - Engineer, R; Ostwal, V; Gupta, P; Chopra, S; Patil, P; Saklani, A; Arya, S; Shrivastava, SK
Abstract : Introduction: The patients with locally advanced unresectable rectal cancers who were still inoperable on MRI imaging were further treated with 4 to 6 cycles of chemotherapy and reassessed for resectability. Method: Patients with locally advanced carcinoma rectum assessed to have unresectable disease on MRI at presentation received neoadjuvant radiation to a dose of 50 Gy in 1.8 to 2 Gy daily fractions with concurrent capecitabine chemotherapy 825 mg/m 2 daily. A follow up MRI was done 6 weeks after completion of NACRT and assessed in a joint multidisciplinary meeting. Those with persisting unresectable local disease on MRI were planned for 4 cycles of chemotherapy followed by reassessment imaging for resectability. We present the results of the patients with poor response to NACTRT having further treated by the chemotherapy. Results: From Jan 2013 till December 2014, 50 patients with unresectable rectal cancer recieving NACRT were still found to have unresectable disease on MRI. They were planned for further chemotherapy with FOLFIRINOX or FOLFOX based regimens. Thirty three (67%) patients had radiological evidence of partial regression and one patient died of neutropenic sepsis. Of these 22 (37%) patients underwent R0 resection and another 10 are scheduled for surgery. Eight patients were still inoperable and 5 were detected to have peritoneal metastasis during surgery were given further palliative chemotherapy. One patient was lost to follow-up and 1 died due to sepsis. Four patients had complete pathological response. Conclusion: Achieving margin negative resection in these patients is an encouraging starting point for further research in this subset. Whether this continued decrease in primary tumour volume can be attributed to delayed response to radiotherapy or addition of further chemotherapy, or both, is yet to be ascertained. Hence for patients with advanced local disease not yet in palliative stage, further intensive chemotherapy with clinicoradiological follow-up should be done to facilitate successful surgical resection. Disclosure of interest: None Declared.